Estratigrafía - Rodríguez, S.; Arribas, M.E.; Comas Rengifo, María Jose; Peña Zarzuelo, A. De la; Falces, S.; Gegúndez, P.; Martínez-Chacón, M.L.; Moreno-Eiris, E.; Perejón, A.; Sánchez, J.L.; Sánchez Chico, Fátima (Coloquios de Paleontología, 1992)
Sin resumen